Ecological Knowledge and Management of Fauna Among the Mexicatl of the Sierra Negra, México: An Interpretive Approach - Zarazúa-Carbajal, Mariana; Chávez-Gutiérrez, Michelle; Peña-Mondragón, Juan Luis; Casas, Alejandro (Frontiers in Ecology and Evolution, 2022)
Management of fauna has taken different shapes throughout the world, generally motivated by the relevance of animals in human subsistence. This study aims to analyse a typology of management forms directed to maintain coexistence and use of fauna and mitigate negative human-fauna interactions by Mexicatl (Nahua) people in Central Mexico. We conducted a qualitative research based on interpretivist approaches, mixing qualitative and quantitative analyses. In 2018 and 2019 we generated 356 free lists of fauna and 20 sessions of group interviews using visual stimuli with children and young people from schools of basic and intermediate levels in five rural communities and the municipal head of Coyomeapan, Puebla. We also generated free lists and in-depth interviews with 18 persons older than 16 years. People recognized 114 animal items, the most salient being 11 domestic and 14 wild animals including deer, medium and small mammals, snakes, and birds. For both domestic and wild fauna people reported 19 use categories and three of damages (crop losses, predation of domestic animals and damages to health). Local Ecological Knowledge (LEK) interacted with traditional celebrations, religious beliefs, land tenure and migration to define preferences and management types of fauna. Bushmeat demand, especially for Mazama temama and Cuniculus paca was related to a healthy nutrition perception. Management actions included husbandry of domestic animals, extraction of wild animals for supply or to avoid damages, captivity, tolerance to damage, protection of seeds and domestic animals threatened by wild fauna without its extraction, regulations for extraction and agreements to prevent conflicts. Mixed quantitative and qualitative approaches allowed interpreting the human-fauna interactions related to subsistence and coexistence and the high relevance of LEK, perceptions, religious beliefs, ecosystem and socio-demographic factors in shaping management practices. Local management strategies of fauna were diverse and contribute to biocultural conservation and theoretical construction on domestication.